2022
DOI: 10.3389/fpsyt.2022.1000722
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal development of depression and anxiety during COVID-19 pandemic in Germany: Findings from a population-based probability sample survey

Abstract: The stress response to the COVID-19 pandemic might differ between early and later stages. Longitudinal data on the development of population mental health during COVID-19 pandemic is scarce. We have investigated mental health trajectories and predictors for change in a probability sample of the general population in Germany at the beginning and after 6 months of the pandemic. We conducted a longitudinal survey in a population-based probability sample of German adults. The current study analyzed data from a fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The results show that symptoms of depression and anxiety (measured with PHQ-4) increased during the first year of the pandemic in the general population and in individuals who were infected with SARS-CoV-2 early in the pandemic. However, this increase remained relatively small, compared with PHQ-4 norm data [7]. Although depression and anxiety seemed on average a little higher in people after SARS-CoV-2 infection compared to persons who did not report an infection, these differences were not significant.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The results show that symptoms of depression and anxiety (measured with PHQ-4) increased during the first year of the pandemic in the general population and in individuals who were infected with SARS-CoV-2 early in the pandemic. However, this increase remained relatively small, compared with PHQ-4 norm data [7]. Although depression and anxiety seemed on average a little higher in people after SARS-CoV-2 infection compared to persons who did not report an infection, these differences were not significant.…”
Section: Discussionmentioning
confidence: 59%
“…We used data collected as part of a population-based longitudinal study with three times of measurement, examining differences between the mental health of people with a SARS-CoV-2 infection in Stuttgart, a large city in southern Germany, and a sample that was representative of the general population in that city [7].…”
Section: Sample and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of literature has therefore aimed to investigate the exact and differentiated impact of the COVID-19 pandemic on mental health. Soon after the pandemics begin in Germany in March 2020 an increase of self-reported psychosocial distress was observed in population-based studies compared to pre-pandemic levels (Giel et al, 2022). Meta-analyses pooling data from international studies reported anxiety and depression levels having the strongest increase during the pandemic (Vindegaar & Benros, 2022; Prati & Mancini, 2021; Robinson et al, 2022).…”
Section: Introductionmentioning
confidence: 99%